Correction to "A Framework for Control System Design Subject to Average Data-Rate Constraints" [Aug 11 1886-1899] - Derpich, Milan S.; Ostergaard, Jan (IEEE transactions on automatic control, 2022)
Theorem 4.1 in the 2011 paper "A Framework for Control System Design Subject to Average Data-Rate Constraints" allows one to lower bound average operational data rates in feedback loops (including the situation in which encoder and decoder have side information). Unfortunately, its proof is invalid. In this note, we first state the theorem and explain why its proof is flawed, and then provide a correct proof under weaker assumptions.